A consistent taxonomic framework: towards common understanding of high energy performance building definitions. (August 2021) - Verhaeghe, C.; Verbeke, S.; Audenaert, A.
Abstract: The rising interest in high energy performance buildings (HEPBs) has led to an inflation of definitions and related terminology to describe them, characterized by (sometimes subtle) differences and overlaps in performance requirements. The wide variety of HEPBs is well worth discussing our approach in distinguishing between them and ensuring common interpretation. Two important tasks we are facing now are the delineation and the classification of HEPB-(sub)types as this is considered to be a critical precondition for generating market trust and understanding of the variety in performance levels of these buildings among the broad range of stakeholders involved. This article presents a taxonomic framework, based on an extended set of relevant key performance indicators and related boundary conditions to report on -and compare- the performance level of HEPBs. The importance of these core indicators and boundary conditions is outlined by means of existing HEPB-definitions. The established taxonomic framework acts as a tool to identify differences and similarities in the HEPB-definitions, which is for instance suitable for the establishment of adequate sets of guidelines, consistent project descriptions and correct categorization of HEPB-(sub)types, contributing to improved communication. The framework is furthermore designed to be flexible to allow for future expansion, and its applicability was tested by means of a selection of existing HEPB-definitions. Highlights: A harmonized definition framework for high energy performance buildings is lacking. Decisive criteria to categorize high energy performance buildings are collected. A consistent taxonomic framework for high energy performance buildings is proposed. The applicability of the taxonomic framework is tested.